2020
DOI: 10.3390/ijms21030745
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Regulation of Myotube Formation and Gene Expression by E2 and EPA during In-Vitro Differentiation of C2C12 Myoblasts

Abstract: Estrogen (E2) and polyunsaturated fatty acids (n-3PUFA) supplements independently support general wellbeing and enhance muscle regeneration in-vivo and myotube formation in-vitro. However, the combined effect of E2 and n-3PUFA on myoblast differentiation is not known. The purpose of the study was to identify whether E2 and n-3PUFA possess a synergistic effect on in-vitro myogenesis. Mouse C2C12 myoblasts, a reliable model to reiterate myogenic events in-vitro, were treated with 10nM E2 and 50μM eicosapentaenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
1
10
1
Order By: Relevance
“…Myoblast proliferation and gene/protein expression of MyoG were reduced at both 48 and 72 h with EPA and DHA treatment ( Zhang et al, 2019 ). In a similar study, using EPA only at the same concentration (50 μM) for 48 h resulted in significantly fewer myotubes, lower fusion index, and reduced expression of MyoD , MyoG , and Tmem8c (myoblast fusion related gene) compared to the control vehicle ( Lacham-Kaplan et al, 2020 ). However, increased expression of Myf6 ( Mrf4 ) and Myf5 was observed.…”
Section: Effects Of Omega-3 Pufa On Myogenic Differentiationmentioning
confidence: 89%
See 3 more Smart Citations
“…Myoblast proliferation and gene/protein expression of MyoG were reduced at both 48 and 72 h with EPA and DHA treatment ( Zhang et al, 2019 ). In a similar study, using EPA only at the same concentration (50 μM) for 48 h resulted in significantly fewer myotubes, lower fusion index, and reduced expression of MyoD , MyoG , and Tmem8c (myoblast fusion related gene) compared to the control vehicle ( Lacham-Kaplan et al, 2020 ). However, increased expression of Myf6 ( Mrf4 ) and Myf5 was observed.…”
Section: Effects Of Omega-3 Pufa On Myogenic Differentiationmentioning
confidence: 89%
“…Overall, the effects of EPA and DHA on the formation of myotube and transcriptional regulation of myogenic differentiation are inconsistent ( Figure 3 ). Three out of the six studies reported a decrease in myotube formation and expression of genes involved in myogenic differentiation ( Myf5 , MyoD , MyoG , and MRF4 ; Hsueh et al, 2018 ; Zhang et al, 2019 ; Lacham-Kaplan et al, 2020 ). On the contrary, three studies ( Saini et al, 2017 ; Shin et al, 2017 ; Xu et al, 2018 ) reported an increase in myotube formation and expression of genes involved in myogenic differentiation with EPA or DHA treatment.…”
Section: Effects Of Omega-3 Pufa On Myogenic Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogen amplifies the effects of retinoids on ameliorating obesity in female mice ( 55 ). Estrogen enhances muscle mass and strength in vivo and promotes muscle regeneration ( 56 , 57 , 58 ). Notably, estrogen action in muscle increases insulin sensitivity, prevents lipid accumulation, and promotes metabolic health ( 59 ).…”
Section: Discussionmentioning
confidence: 99%